Flavors' Decreasing Contribution to p‐Anisidine Value over Shelf Life May Invalidate the Current Recommended Protocol for Flavored Fish Oils. (14th October 2020) - Ye, Liyun; Harris, Emily; Budge, Suzanne M.; Sullivan Ritter, Jenna
Abstract: The American Oil Chemists' Society (AOCS) Official Method Cd 18–90 for p ‐Anisidine Value (pAV) is commonly used to evaluate secondary oxidation in fish oils. Flavoring agents in fish oil products may interfere with pAV and lead to inaccurate results. The Global Organization for EPA and DHA (GOED) recommends a protocol for calculating pAV of flavored fish oils based on the assumption that flavors' contribution to the pAV does not change over the course of oxidation. The objective of this study was to test this assumption. All 14 flavors evaluated increased the pAV when added to fresh fish oil; chocolate‐vanilla and lemon flavors generated the largest increase. Under accelerated oxidation conditions, both chocolate‐vanilla and lemon flavors had a similar effect; oxidized flavored fish oils had lower pAV than oxidized fish oils with newly added flavors. This was due to either an antioxidant effect of the flavor or loss of the flavor during oxidation. Following the GOED recommendation, we would have underestimated the oxidation in the flavored oils. For this reason, the pAV of flavored fish oils should be considered with caution and used in combination with other secondary oxidation markers when possible.